Implementation of Regional Regulation Number 10 of 2017 on Waste Management (A Study at the Environmental Agency of Dompu Regency) - Rahmania, Nurul; Abdurrahman, Abdurrahman; S, M. Ariy Dermawan (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2025)
Waste management in Dompu Regency remains a major challenge in achieving a clean and healthy environment. Although Regional Regulation Number 10 of 2017 concerning Waste Management has been issued, the implementation of this policy has not yet produced optimal results. This study aims to analyze the implementation of the regulation and identify the supporting and inhibiting factors affecting its execution. The research employs a descriptive qualitative approach with data collection techniques including field observations, in-depth interviews, and documentation. The findings indicate that the main obstacles to policy implementation include a lack of public outreach, limited facilities and infrastructure, weak inter-agency coordination, and insufficient budgetary support. On the other hand, the commitment of technical implementers on the ground serves as a foundational asset for achieving a sustainable waste management system. Therefore, strategies such as strengthening institutional capacity, continuous public education, and enhanced cross-sector coordination are necessary to support the success of this policy.